Assessment of Development Results - Senegal - Programme des Nations Unies pour le Développement (United Nations, 2011)
This report presents an independent country-level evaluation conducted by the UNDP Evaluation Office in 2010. The evaluation examines the strategic relevance and positioning of UNDP support, and its contribution to the development of Senegal